Оцінка ефективності кредитування підприємства - Котлярова, Ангеліна Вікторівна; Мільшина, В. М. (НТУ "ХПІ", 2010)
Вопрос выбора источников финансирования возникает на каждом предприятии. Главной является задача установления баланса между собственными и заемными средствами, особенно в условиях убыточности или низкой рентабельности предприятий. Оценка эффективности кредитования предприятия с помощью коэффициента финансового левериджа позволяет установить порог, за которым наращивание заемных средств нецелесообразно.

The questions of the correct choice of financing sources emerge at each enterprise. The problem of establishment of balance between own and loan proceeds is important, especially if the enterprises are influenced by negative conditions like unprofitableness or low profitability. The estimation of enterprise crediting efficiency, which is acomplished by estimation of financial leverage ratio and calculation of indicator of efficiency financial leverage ratio, helps to establish such a threshold that having reached it escalating of loan proceeds is inexpedient.
Keywords: господарська діяльність; прибуток; рентабельність активів; кредитування; фінансовий леверидж; власний капітал; позикові кошти